Financing Activity of the European Investment Bank in the Danube Region - Hagiu, Alina; Barbulescu, Marinela (Journal of Danubian Studies and Research, 2022)
The European Union supports the Danube Region because it has nine EU Member States (Austria, Bulgaria, Croatia, the Czech Republic, Germany, Hungary, Romania, Slovakia and Slovenia) and five non-EU countries (Bosnia-Herzegovina, Montenegro, Serbia, Moldova, Ukraine). In this sense it has developed a macro-economic strategy to strengthen cross-border cooperation in the Danube Region. The EIB is fully supporting this strategy. In this paper we aim to analyze the role and importance of the financial support given by the EIB to the countries in the Danube Region.